Assessment of fully automated antibody homology modeling protocols in molecular operating environment. Issue 8 (23rd April 2014) - Maier, Johannes K. X.; Labute, Paul
ABSTRACT The success of antibody‐based drugs has led to an increased demand for predictive computational tools to assist antibody engineering efforts surrounding the six hypervariable loop regions making up the antigen binding site. Accurate computational modeling of isolated protein loop regions can be quite difficult; consequently, modeling an antigen binding site that includes six loops is particularly challenging. In this work, we present a method for automatic modeling of the FV region of an immunoglobulin based upon the use of a precompiled antibody x‐ray structure database, which serves as a source of framework and hypervariable region structural templates that are grafted together. We applied this method (on common desktop hardware) to the Second Antibody Modeling Assessment (AMA‐II) target structures as well as an experimental specialized CDR‐H3 loop modeling method. The results of the computational structure predictions will be presented and discussed. Proteins 2014; 82:1599–1610. © 2014 The Authors. Proteins published by Wiley Periodicals, Inc.